The usage of mineral waters in Bulgaria as a factor for the development of the municipalities (Research Announcements "Heritage BG", 2025)
The main goal of this study is an analysis of the use of mineral waters in Bulgaria as a factor for the development of municipalities, increasing the quality of life of local residents and the development of mineral water-related tourism. The research is based on data from strategic documents of municipalities, interviews with their representatives, local residents and local business representatives. The relevance of the topic stems from the fact that the management of mineral waters faces a number of problems that create obstacles to their rational use. The results show that these problems are mainly related to administrative procedures and institutions responsible for mineral waters, as well as to regulatory requirements. The main recommendation is that in order to make full use of the mineral water resource, a national strategy, policy, comprehensive management approach and investment is needed to solve the identified problems at both macro and local levels. References:Aleksandrova 2023: Aleksandrova, Nina. From one water body in Sofia, 8 litters per second are poured into the sewer, 22.03.2023. Available at: https://kmeta.bg/%d0%be%d1%82-%d0%b5%d0%b4%d0%bd%d0%be-%d0%b2%d0%be%d0%b4%d0%bd%d0%be-%d0%bd%d0%b0%d1%85%d0%be%d1%89%d0%b5-%d0%b2-%d1%81%d0%be%d1%84%d0%b8%d1%8f-%d1%81%d0%b5-%d0%b8%d0%b7%d0%bb%d0%b8%d0%b2/Bilyarska 2018: Bilyarska, Radostina. Experts: A law on mineral waters and investments for the management of springs are needed Available at: https://bnr.bg/horizont/post/100950466/eksperti-po-vodite-neobhodim-e-zakon-za-mineralnite-vodi-i-investicii-za-stopanisvane-na-izvoriteDineva 2022: Dineva, Detelina. They discuss the development of a strategy for the use of mineral waters in Bulgaria. 19.07.2022. Available at: https://www.iskra.bg/obsazhdat-razrabotvane-na-strategia-za-izpolzvaneto-na-mineralnite-vodi-v-balgaria/Explica – Global Metrics 2019: Eksplika-Global Metriks DZZD (2019). Health tourism. Products’ analysis (In Bulgarian). Available at: https://www.tourism.government.bg/sites/tourism.government.bg/files/Gencheva 2023: Gencheva, Boriyana. Star season for Bulgarian spa resorts – new luxury hotels, more tourists and higher prices, V-k Kapital, may 2023 г. Available at: https://www.capital.bg/biznes/turizum/2023/05/20/4480414Ivanova 2023: Ivanova, Venelina. Bulgaria can support itself entirely from our mineral waters, 15.07.2023. Available at: https://www.bta.bg/bg/news/economy/490238-balgariya-mozhe-da-se-izdarzha-samo-ot-mineralnite-ni-vodiStoyanov 2023: Stoyanov, Nikola. The fate of the mineral baths was discussed at a round table 26.01.23. Available at: https://bnr.bg/sofia/post/101770479/sadbata-na-mineralnite-bani-beshe-obsade%adna-na-kragla-masaZhikov 2023: Zhikov, Georgi. A Vidin deputy requested a state strategy for mineral springs. 17.01.23. Available at: https://bnr.bg/vidin/post/101765572/diskusia-za-mineralnite-izvori-se-provede-v-narodnoto-sabranieBennett et al. 2004: Bennett, Michelle, King, E.M. Brian, Milner, Laura. The health resort sector in Australia: A positioning study. Journal of Vacation Marketing, 10(2), 122-137. DOI: 10.1177/135676670401000203Butler 1980: Butler, W. Richard. The concept of a tourist area cycle of evolution: Implications for management of resources. Canadian Geographer, XXIV, 1, 1980, 5-12. DOI: https://doi.org/10.1111/j.1541-0064.1980.tb00970.xCheshemdzhiev 2021: Chesmedzhiev, Krassimir. Geothermal energy in Bulgaria? Yes, but be careful with mineral water, 12.08.2021 г. Available at: https://www.bloombergtv.bg/a/57-bloomberg-tv-bulglaria-intervyu/96759-promyana-v-temperaturata-na-termo-mineralnite-vodi-do-promeni-fizikohimichniya-sastavCohen & Bodeker 2008: Cohen, Mar, Bodeker, Gerard (Eds.). Understanding the Global Spa Industry. Amsterdam: Elsevier.Smith & Puczko 2008: Smith, Melanie, Puczko, Laszlo. Health and Wellness Tourism. London: Routledge.Tabacchi 2010: Tabacchi, H. Mary. Current Research and Events in the Spa Industry. Cornell Hospitality Quarterly, 51(1), 102-117. https://doi.org/10.1177/1938965509356684Online documents:Council of Ministers Decision No. 153 of February 24, 2012 (In Bulgarian) za obyavyavane Spisak na kurortite v Republika Bulgaria i opredelyane na tehnite granitsi. Available at: http://www.dv.parliament.bg/DVWeb/showMaterialDV.jsp;jsessionidFrom ‘God’s bath’ to the spa (In Bulgarian) Available at: https://www.google.com/search?q=https://www.palacesofhealth.com/bg/%25Health Tourism Development Plan (2022-2025) (In Bulgarian) Available at: https://www.tourism.government.bg/sites/tourism.government.bg/files/Ministry of Environment and Waters (In Bulgarian)  Available at: https://www.moew.government.bg/bg/vodi/mineralni-vodi/mineralni-vodi/National Concession Register (as of 08.2023) (In Bulgarian), Available at: https://nkr.government.bg/ConcessionsNational Strategy for the Sustainable Development of Tourism in the R of Bulgaria 2014-2030 (In Bulgarian) Available at: https://www.tourism.government.bg/sites/tourism.government.bg/files/Ordinance No. 1 of 10.10.2007 (In Bulgarian) Available at: https://lex.bg/laws/ldoc/2135569070Water Law (In Bulgarian) Available at: https://lex.bg/laws/ldoc/2134673412/
Keywords: mineral waters; municipalities; Bulgaria; health tourism; problems